Health behaviour, social support, socio-economic status and the 5-year progression of multimorbidity: Results from the MultiCare Cohort Study. (21st October 2019) - Schäfer, Ingmar; Hansen, Heike; Kaduszkiewicz, Hanna; Bickel, Horst; Fuchs, Angela; Gensichen, Jochen; Maier, Wolfgang; Riedel-Heller, Steffi G; König, Hans-Helmut; Dahlhaus, Anne; Schön, Gerhard; Weyerer, Siegfried; et al.
Background: Multimorbidity in elderly patients is a major challenge for physicians, because of a high prevalence of and associations with many adverse outcomes. However, the mechanisms of progressing multimorbidity are not well-understood. The aim of our study was to determine if the progression of multimorbidity is influenced by health behaviour and social support and to analyse if the patients' socio-economic status had an effect on these prognostic factors. Methods: The study was designed as prospective cohort study based on interviews of 158 GPs and 3189 patients randomly selected from GP records (response rate: 46.2%). Patients were aged 65–85 years at recruitment and observed in four waves of data collection (dropout rate: 41.5%). Statistical analyses of the 'hot deck' imputed data included multilevel mixed-effects linear regression allowing for random effects at the study centre and GP practice within study centre level. Results: Regarding cardiovascular and metabolic diseases, multimorbidity progressed more rapidly in patients who reported less physical activity ( ß = −0.28; 95% confidence interval = −0.35 to −0.20), had more tobacco-related pack years (0.15; 0.07–0.22) and consumed less alcohol (−0.21; −0.31 to −0.12) at baseline. Multimorbidity related to psychiatric and pain-related disorders progressed more rapidly if the patients had less perceived social support (−0.31; −0.55 to −0.07) and reported less physical activity (−0.08; −0.15 to −0.02) at baseline. Education and income only slightly modified the effects of these variables. Conclusion: Depending on the multimorbidity cluster, different strategies should be used for slowing down the progression of multimorbidity. Changing lifestyle and increasing social support are beneficial for the entire group of elderly multimorbid patients – regardless of their socio-economic status. Registration: ISRCTN89818205